Perlindungan Gedung Perwakilan Diplomatik Republik Indonesia Dalam Konflik Bersenjata di Yaman - Rusvinna Rizky Hariyanti; Arman Anwar; Dyah Ridhul Airin Daties (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The diplomatic representative building is a place used to carry out all activities related to the mission of diplomatic officials and has been protected by law. But in reality, the diplomatic mission building has always been the target of armed conflict and caused such destruction that diplomatic representatives could not carry out their duties properly.Purposes of the Research: Know and analyze the protection arrangements of diplomatic representative buildings according to the Vienna Convention on Diplomatic Relations 1961. Methods of the Research: The research method used is normative legal research by reviewing legal literature using statutory regulations, case approaches and conceptual approaches.Results of the Research: The results of the research showed that the diplomatic representative building is legally protected under Article 22 of the Vienna Convention on Diplomatic Relations 1961. The convention obliges the receiving state to take all steps to protect the mission building against intrusion or destruction. This obligation applies even if the receiving country is in an armed conflict, whether international or non-international. The armed conflict in Yemen caused the destruction of the Indonesian diplomatic representative building. Therefore, Yemen as a receiving country is considered negligent in carrying out protection and is required to be responsible internationally.